Blockchain applications in business and financial activities in Vietnam: Situation, trends, opportunities and challenges - Bao, Truong Gia; Phan, Dat Minh (International research journal of management, IT and social sciences, 2022)
The emergence and rapid development of blockchain technology is an important milestone in the development of every country across the world. In Vietnam, blockchain is applied in many aspects of life, such as finance, banking, business, commerce, e-commerce, tourism, education, and healthcare. Previously, blockchain was known as the origin of cryptocurrencies. However, in recent years, blockchain technology and its applications have gone far beyond cryptocurrencies. This study aimed to assess the current situation, development trends, opportunities, and challenges in applying blockchain in business and financial activities. The research analyzed the Vietnamese government’s policies related to blockchain technology. In addition, the study updates the development trends of blockchain technology in business and financial activities through international scientific conferences, books, newspapers, and magazines. The study’s findings indicate that Vietnam is a high potential market for developing blockchain technology. Also, Vietnam faces many opportunities and challenges in catching up with this trend, especially when Vietnam is implementing many policies to develop the digital economy. Therefore, thanks to assessing the current situation, development trends, opportunities, and challenges in Vietnam, the study helps to suggest some solutions for the difficulties in applying blockchain technology, especially the thirst for human resources in the blockchain industry.